Different patterns of the photosynthetic apparatus recovery during early rehydration following drought stress in two types of intergeneric hybrid of triticale - Ostrowska, Agnieszka; Hura, Katarzyna; Hura, Tomasz (Environmental and experimental botany, 2023)
The study aimed to reveal the activity of the photosynthetic apparatus during early rehydration in double haploid (DH) lines of triticale with different types of flag leaf rolling in response to soil drought. Two DH lines, showing full (Type O) and limited (Type V) flag leaf rolling, were investigated. The measurements of chlorophyll fluorescence, analysis of red/far-red fluorescence excitation spectra, as well as detection of selected PSII proteins (PsbA/D1, PsbS) and transmembrane cytochrome complex b6f (PetC/Rieske protein) were performed. The measurements were carried out on the last day of drought and after 1 h, 3 h, and 5 h of rehydration. The physiological condition of flag leaves was studied based on measurements of water relations, the progress of leaf senescence, histochemical detection of reactive oxygen species, and the content of sugars and phenolic compounds. In Type O, as compared with Type V, a further decline in the activity of the photosynthetic apparatus was observed during the post-drought rehydration period. This was accompanied by the accumulation of reactive oxygen species and more advanced senescence of flag leaves. Fluorescence excitation spectra revealed disorders in photosynthetic light conversion in Type O flag leaves during drought and rehydration over the entire range of excitation wavelengths corresponding to UVC, UVB, and UVA radiation. Type V flag leaves developed an effective UV protection mechanism in the form of increased accumulation of cell wall-bound phenolics, which efficiently absorbed UV radiation. Both types differed in the level of accumulation of PsbA, PsbS, and PetC proteins during drought and early rehydration. Soil drought caused a similar reduction in grain yield in both types. However, in Type O, the largest share in the grain yield was ascribed to the ears of lateral stems, while in Type V to the ears of the main stems. Our research has shown that the limited rolling of flag leaves under drought stress corresponds to the effective photoprotection of the photosynthetic apparatus in the first hours of rehydration. •The activity of the photosynthetic apparatus was analyzed during drought and early rehydration.•Studied genotypes exhibited full (Type O) or limited (Type V) flag leaf rolling under drought stress.•Fluorescence excitation spectra revealed disorders in photosynthetic light conversion in Type O.•Type V flag leaves developed an effective protection mechanism against UVC, UVB, and UVA radiation.•Differences in the accumulation of PSII proteins and cytochrome b6f complex were observed.